Pancreatic Inflammatory Pseudotumor-Like Follicular Dendritic Cell Tumor - Madison Mograbi; Michael S. Stump; David T. Luyimbazi; Mohammad H. Shakhatreh; Douglas J. Grider (Case Reports in Pathology)
Follicular dendritic cell sarcoma (FDCS) is a rare and underdiagnosed malignant neoplasm which characteristically presents as a solitary, slow-growing mass with no discrete symptoms. Histologically, lymphocytes and spindle cells featuring large nucleoli in a whorled pattern are usually seen. FDCS is classically found in cervical and axillary lymph nodes, with occasional involvement of extranodal sites. Inflammatory pseudotumor-like follicular dendritic cell tumor (IPT-like FDCT) is an uncommon subcategory of this neoplasm, demonstratively linked to the Epstein-Barr virus (EBV). This neoplasm can present similarly to FDCS, but systemic symptoms may be seen. Although, often found in the spleen and occasionally the liver, IPT-like FDCT has not previously been described within the pancreas. Presented, is an IPT-like FDCT of the pancreas and spleen of a 70 years old woman. Histologic features include variably sized geographic suppurative granulomas with chronic inflammatory cells and an atypical spindle cell proliferation with prominent nucleoli. Positivity for CD45 and CD68 in the larger spindled cells points to an inflammatory pseudotumor subtype and co-expression of CD21, CD23, and CD35 were indicative of follicular dendritic differentiation. The pseudotumor additionally demonstrated EBV-encoded RNA (EBER) positivity typical of IPT-like FDCT. Differentiation between inflammatory pseudotumor (IPT) and inflammatory myofibroblastic tumor (IMT) is additionally discussed.